Treatment of opioid dependence with depot buprenorphine (CAM2038) in custodial settings. (16th July 2021) - Dunlop, Adrian J.; White, Bethany; Roberts, Jillian; Cretikos, Michelle; Attalla, Dena; Ling, Rod; Searles, Andrew; Mackson, Judith; Doyle, Michael F.; McEntyre, Elizabeth; Attia, John; Oldmeadow, Christopher; et al.
Abstract: Background and aims: Opioid agonist treatment is effective but resource intensive to administer safely in custodial settings, leading to significant under‐treatment of opioid dependence in these settings world‐wide. This study assessed the safety of subcutaneous slow‐release depot buprenorphine in custody. Design: Open‐label, non‐randomized trial. Setting: Correctional centres in New South Wales, Australia. Participants: Sixty‐seven men and women, aged ≥ 18 years of various security classifications with a diagnosis of moderate to severe DSM‐5 opioid use disorder currently serving a custodial sentence of ≥ 6 months were recruited between November 2018 and July 2019. Patients not in opioid agonist treatment at recruitment commenced depot buprenorphine; patients already stable on oral methadone treatment were recruited to the comparison arm. Intervention and comparator: Depot buprenorphine (CAM2038 weekly for 4 weeks then monthly) and daily oral methadone. Measurements: Safety was assessed by adverse event (AE) monitoring and physical examinations at every visit. Participants were administered a survey assessing self‐reported diversion and substance use at baseline and weeks 4 and 16. Findings: Retention in depot buprenorphine treatment was 92.3%. Ninety‐four per cent of patients reported at least one adverse event, typically mild and transient. No diversion was identified. The prevalence of self‐reported non‐prescribed opioid use among depot buprenorphine patients decreased significantly between baseline (97%) and week 16 (12%, odds ratio = 0.0035, 95% confidence interval = 0.0007–0.018, P  < 0.0001). Conclusions: This first study of depot buprenorphine in custodial settings showed treatment retention and outcomes comparable to those observed in community settings and for other opioid agonist treatment used in custodial settings, without increased risk of diversion.